Continuous glucose monitoring reveals hypoglycemia risk in elderly patients with type 2 diabetes mellitus. Issue 1 (24th May 2017) - Ishikawa, Takahiro; Koshizaka, Masaya; Maezawa, Yoshiro; Takemoto, Minoru; Tokuyama, Yoshiharu; Saito, Toshihiro; Yokote, Koutaro
Abstract : We utilized a continuous glucose monitoring (CGM) device to analyze the relationship between hypoglycemia and diabetes treatments to identify risk factors for hypoglycemia (defined as a blood glucose level <70 mg/dL). In patients aged ≥65 years with type 2 diabetes, higher glucose variability and lower average glucose levels indicate a greater hypoglycemia risk. It is therefore necessary to ensure comprehensive blood glucose control in such patients to prevent hypoglycemia. Abstract: Aims/Introduction: The incidence of type 2 diabetes is higher in elderly patients, in whom this disease is associated with dementia, falling, stroke and death. We utilized a continuous glucose monitoring device to analyze the relationship between hypoglycemia and diabetes treatments to identify risk factors for hypoglycemia (defined as a blood glucose level <70 mg/dL). Materials and Methods: We classified 170 patients aged ≥65 years with type 2 diabetes who were receiving steady‐state medication (29 of whom were inpatients) into hypoglycemic and non‐hypoglycemic groups, and compared their glycosylated hemoglobin levels, treatment types, continuous glucose monitoring data and other parameters. We carried out univariate analyses to identify variables associated with hypoglycemia risk, followed by multivariate analyses of drug class and other factors. The accuracy of the continuous glucose monitoring data was confirmed by calibration. Results: Hypoglycemia risk was higher in the patients using insulin (odds ratio [OR] 2.17, 95% confidence interval [CI] 1.16–4.08, P = 0.015), and lower in patients who were being treated with dipeptidyl peptidase‐4 inhibitors (OR 0.47, 95% CI: 0.25–0.89, P = 0.019). Patients with lower variability in blood glucose had a significantly lower hypoglycemia risk (OR 0.87, 95% CI: 0.83–0.91, P < 0.0001), and those with a lower average blood glucose level had a significantly higher risk (OR 1.09, 95% CI: 1.06–1.12, P < 0.0001). Conclusions: In patients aged ≥65 years with type 2 diabetes, higher glucose variability and lower average glucose levels indicate a greater hypoglycemia risk. It is therefore necessary to ensure comprehensive blood glucose control in such patients to prevent hypoglycemia.